Standardization and Analytical Profiling of Shirashooladi Vajra Rasa: A Comparative Study with Marketed Samples (International Journal of Ayurveda and Pharma Research, 2025)
Shirahshooladi vajra rasa is a potent mercurial preparation widely used in the treatment of Shirahshoola (headache). It consists of processed mercury and sulphur, incinerated copper and iron along with other herbal ingredients like Triphala, Yastimadhu, Pippali, Shunthi, Vidanga, Dashamula and Guggulu. This formulation is enriched with Vatashamaka (mitigates Vata dosha) herbs like Dashamula, Guggulu etc. Aim and objective: This study aims at developing standard manufacturing procedure (SMP) and analytical parameters of Shirahshooladi vajra rasa along with analysis of its available marketed samples. Methodology: The formulation was prepared in three batches to standardize its pharmaceutical processing. Also, six other available different samples of the Shirashooladi vajra rasa were collected from market and all the seven samples were assessed for quality control parameters to compare their quality. Observations & Result: All the quality control parameters conducted for inhouse and marketed samples were not similar, some variations were found. Conclusion: The average yield obtained from three batches is 99.1%. Analytically, slight variation was observed among all the samples.